2010
DOI: 10.1103/physrevb.82.041403
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of peapod-derived double-walled carbon nanotubes

Abstract: Atomistic simulations and a dislocation-based analysis reveal the mechanism of carbon peapod fusion into double-walled nanotubes. They explain the trend of diameter increase for the emerging inner wall, driven by the reduction in its strain energy and the interwall van der Waals energy. Surprisingly, this is also accompanied by the systematic bias in the nanotube chirality, changing from zigzag toward armchair. This prediction agrees well with our experimental data and is further supported by the analysis of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…38 The agreement 75 between these theoretical predictions and experimental measurements validated the EDKMC method. 38 Beyond, previous study has shown that the space constrain of outer tube plays a crucial role in the inner tube formation. The final inner tube always tends to fit the outer tube with a wall-wall distance range of 0.34-0.38 nm, which is exact the same as the experimentally observed wall-wall distance of DWNTs.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…38 The agreement 75 between these theoretical predictions and experimental measurements validated the EDKMC method. 38 Beyond, previous study has shown that the space constrain of outer tube plays a crucial role in the inner tube formation. The final inner tube always tends to fit the outer tube with a wall-wall distance range of 0.34-0.38 nm, which is exact the same as the experimentally observed wall-wall distance of DWNTs.…”
mentioning
confidence: 66%
“…More details of the EDKMC 35 method and its validity are shown in previous publication. 38 In previous studies, we have shown that there's no tube chiral angle correlation between the inner wall tube and outer wall tube and thus a (18, 0) SWNT was chosen as the only outer wall tube in all trajectories. The Monte Carlo temperature of all trajectories was 40 set as 2000 K, which is close to the experimental temperature of deriving peapods into DWNTs.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations